Interpreting EU Funds Data for Macroeconomic Analysis in the New Member States - Sierhej, Robert (IMF Working Papers; Working Paper ;, 2007)
Drawing on a dataset suitable for macroeconomic analysis, the paper provides an overview of the magnitudes, purpose and institutional implications of EU-related transfers to and from the new member states. A rough analysis of accounting identities and first-round effects shows that EU funds may have led to a fiscal drag of up to 1 percent of GDP and an additional aggregate demand stimulus of up to 1 percent of GDP during the first years of membership. These effects are likely to increase as additional funding become available under the new financial perspective, pointing to the need to consider policy tradeoffs.